Pengembangan Kemampuan Kognitif Anak Usia Dini melalui Permainan Edukatif di KB Mentari Kebonagung - Wiji Setyani; Eka Danik Prahastiwi (MASALIQ, 2026)
The development of early childhood cognitive abilities is an important aspect of early childhood education, particularly through learning activities that are concrete, enjoyable, and appropriate to children’s developmental stages. This study aims to describe the implementation of educational games and analyze the development of early childhood cognitive abilities at KB Mentari Kebonagung. This study used a descriptive qualitative approach with a case study design. The research subjects consisted of eight children aged 3–4 years. Data were collected through participant observation, in-depth interviews, and documentation, with an observation sheet based on the indicators of the Child Development Achievement Level Standards (STPPA) used as the instrument. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results show that educational games are implemented regularly and structurally through various media, such as puzzles, blocks, number cards, and matching games. The development of children’s cognitive abilities showed positive results, with most children reaching the categories of Developing as Expected (BSH) and Developing Very Well (BSB), particularly in the aspects of recognizing colors and shapes, number concepts, and the ability to classify objects. However, variations in development were still found in the aspect of simple problem-solving. Supporting factors in the implementation of educational games include the availability of media and teacher competence, whereas inhibiting factors include limited facilities and low parental involvement. This study concludes that educational games are effective in supporting the improvement of early childhood cognitive abilities. These findings provide practical implications for early childhood education teachers in designing game-based learning that is structured, contextual, and appropriate to children’s developmental needs.